Reproductive Activity of Tsigaie Sheep Belonging to the Hill and Mountain Ecotypes - Vasile Miclea; Marius Zăhan; Vasile Rău; Alexandru Nagy; Ileana Miclea (Scientific Papers Animal Science and Biotechnologies, 2023)
The reproductive value of sheep belonging to the hill and mountain ecotypes of the Tsigaie breed was characterized based on the analysis of specific indexes. This operation was deemed necessary given our interest in the ex situ conservation of these ecotypes. Our research resulted in establishing that the hill ecotype is superior to the mountain ecotype, as is apparent by comparing indices for the two. The number of sheep in oestrus is higher by 9.56%, the pregnancy rate by 9.14%, the insemination index by 37.11%, the index of abortions by 6.96%, the fertility index by 19.76%, the sterility index by 14.18% and the number of lambed sheep by 15.06%. Only the prolificacy index is higher in the mountain ecotype by 5.96%. This situation stems from the particular biology of each ecotype and warrants optimal keeping and feeding for the mountain ecotype so that future research will not negatively influenced.